Nurses’ perception on Initial Implementation of Early Warning System: A Mixed Method Study - Sujalmo, Purwadi; Setiyarini, Sri; Walsh, Kenneth; Greenwood, Melanie (Fakultas Ilmu-ilmu Kesehatan, 2022)
The early warning system (EWS) has been decided as a new standard for Indonesian hospitals. The main objective of EWS implementation is to help nurses quickly recognize and react to deteriorating patients. This study explores how EWS contributes to nurses’ clinical decisions around patient deterioration. The research design for this study was mixed-method sequential explanatory. A purposive sampling approach was used to recruit the participants. Closed and open-ended questionnaires were distributed (n = 53) to adult unit nurses and the data was analyzed by using descriptive statistics. Focus group discussions were conducted to evaluate the implementation process and the results obtained were analyzed by using thematic analysis. Both data were integrated by using a joint display table. We found that 79% of nurses indicated that they needed education about how to use the EWS and 92% of nurses required education on physiology and management of the deteriorating patient. Three themes emerged: (1) the nurses’ experience of EWS Implementation, (2) the impact of EWS implementation, and (3) ameliorating the EWS Implementation. The participants showed that the EWS has been used for the assessment, documentation, and communication process of deteriorating patient management. The EWS is a complex tool for nurses, and they need support from stakeholders to maintain and optimize the advantages.